AB0648 The effects of end stage renal failure on lupus disease activity. (23rd January 2014) - Wincup, C.; McGuinness, D.; McLean, A.; Lightstone, L.
Abstract : Background: Systemic lupus erythematosus (SLE) is a systemic autoimmune disorder characterised by failure to regulate pathogenic autoantibody production against nuclear and cytoplasmic components. Manifestations of SLE can be widespread, affecting a number of organ systems. One of the most serious complications of SLE is lupus nephritis (LN), which develops in approximately 60% of patients with SLE. Depending on ethnicity 10-40% of patients with LN will develop end stage renal disease (ESRD). Previous studies have suggested that once ESRD is reached, SLE disease activity decreases and patients have fewer symptoms. It has been speculated that this may be due to uraemia leading to decreased cellular and humoral immunity. Objectives: This study aims to look at SLE disease activity in patients who have reached ESRD due to LN and have required renal replacement therapy (RRT) with dialysis or transplantation. Methods: A retrospective analysis of notes and data of all patients alive in Jan '11 with a diagnosis of ESRF due to LN, either on dialysis (Dx) or transplanted (Tx) between Nov '05 and Jan '11 in the Imperial College Healthcare NHS Trust Renal & Transplant Centre. Outcomes included clinical symptoms (alopecia, arthralgia, rash, serositis, cerebritis, fevers), and serological markers of disease activity (complement, dsDNA, platelet count, polymorph count), and levels of immunosuppression required. Results: 53 patients were identified for analysis (45 female, 8 male) from a variety of ethnicities (White 20, Black 16, Asian 9, Other 8). The median time from SLE diagnosis to ESRD was 36 months - however 12 patients reached ESRD at first presentation. Of the patients identified 34 had functioning Tx, 15 patients were on Dx and 4 had died. SLE disease activity was noted to remain prevalent in patients following the onset of ESRD. 43.4% of patients suffered at least one flare of disease following ESRD. Many patients had more than one system involvement of which the most common was arthralgia (15/53). Dermatological (22.6%) and haematological manifestations (20.8%) were also common in patients after the onset of ESRD. In addition cerebral SLE flares were noted in 3 patients and alopecia was described in a further 5. Furthermore low complement (43.4%) and raised dsDNA (41.5%) were common. Of the 16 with both low complement and high dsDNA, 69% had flares. Thrombocytopenia was noted in 15.1% of patients following the onset of ESRD. Immunosuppressive management in patients on RRT was also noted to be different from those that had undergone Tx. Patients on Dx were usually managed with oral steroids, whereas patients that received transplantation were immunosuppressed with tacrolimus in the majority of cases. 4 additional transplant patients were treated with additional MMF. 2 patients who had undergone renal transplantation subsequently suffered recurrence of lupus nephritis and lost their transplanted graft. Conclusions: It has previously been suggested that lupus disease activity decreases following the onset of ESRD. However this data shows that SLE does remain active in patients on RRT/having undergone Tx. This may be due to improved management of uraemia with dialysis and steroid-sparing immunosuppression in transplant patients. Specialists involved in the care of patients with SLE should be aware of the potential of persistent disease activity in patients on RRT who were previously felt to be quiescent regarding their underlying disease. Disclosure of Interest: None Declared